Additional Meals at the Wedding Ceremony in Nagari Tandikek, Patamuan District, Padang Pariaman District - Hakim, Arif; Nursaid, Nursaid; Suhaili, Samsudin; Ningsih, Ayu Gustia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Pasambahan dining is a unique tradition that symbolizes the rich culture and local wisdom of the local community. In this ceremony, various types of typical food are served on banana leaves and traditional kitchen utensils, symbolizing respect for ancestors and harmony with nature. This tradition also illustrates the values of solidarity, mutual cooperation and brotherhood that are unique to the Nagari Tandikek community. Even though times are developing, the essence of the Pasambahan eating tradition is still maintained and preserved as a regional cultural identity. This article discusses the details and philosophy contained in the pasambahan eating tradition, as well as its development in modern life.